Teaching literacy to learners with dyslexia :A multisensory approch - Kelly, Kathleen S. (SAGE, 2011)
Provides a structured program--including strategies, activities, reproducible resource sheets, and downloadable materials--for teaching literacy skills to children and young people (ages 5 to 18) with dyslexia or specific learning difficulties.